The Relevance of Defining Terrorism: Exploring the Causes and Challenges of Defining Terrorism (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The sheer volume and variety of definitions of the phenomenon of terrorism signifies the importance it has gained in the lives of society and state. However, universally accepted definitions are yet to be arrived at. This writing is an attempt to seek the causes and problems of this scarcity.